[11C]PK11195 binding in Alzheimer disease and progressive supranuclear palsy. (29th May 2018) - Passamonti, Luca; Rodríguez, Patricia Vázquez; Hong, Young T.; Allinson, Kieren S.J.; Bevan-Jones, W. Richard; Williamson, David; Jones, P. Simon; Arnold, Robert; Borchert, Robin J.; Surendranathan, Ajenthan; Mak, Elijah; Su, Li; et al.
Abstract : Objective: We tested whether in vivo neuroinflammation relates to the distinctive distributions of pathology in Alzheimer disease (AD) and progressive supranuclear palsy (PSP). Methods: Sixteen patients with symptomatic AD (including amnestic mild cognitive impairment with amyloid-positive PET scan), 16 patients with PSP–Richardson syndrome, and 13 age-, sex-, and education-matched healthy controls were included in this case-control study. Participants underwent [ 11 C]PK11195 PET scanning, which was used as an in vivo index of neuroinflammation. Results: [ 11 C]PK11195 binding in the medial temporal lobe and occipital, temporal, and parietal cortices was increased in patients with AD, relative both to patients with PSP and to controls. Compared to controls, patients with PSP showed elevated [ 11 C]PK11195 binding in the thalamus, putamen, and pallidum. [ 11 C]PK11195 binding in the cuneus/precuneus correlated with episodic memory impairment in AD, while [ 11 C]PK11195 binding in the pallidum, midbrain, and pons correlated with disease severity in PSP. Conclusions: Together, our results suggest that neuroinflammation has an important pathogenic role in the 2 very different human neurodegenerative disorders of AD and PSP. The increase and distribution of microglial activation suggest that immunotherapeutic strategies may be useful in slowing the progression of both diseases.